Synthesis of Fatty and N,N'-carbonyl Difatty Amides from Palm Oil and Their Applications as a Clay Modifier for Polylactic Acid/Epoxidized Palm Oil/Clay Nanocomposites Preparation - Jaffar Al-Mulla, Emad A. (2010)
N,N-carbonyl difatty amides (CDFAs) were synthesized from palm oil and urea using sodium ethoxide as a catalyst. Ethyl fatty esters (EFEs) and glycerol were produced as by-products. The synthesis was carried out by refluxing the reactants in ethanol. In this reaction, palm oil gave 79% CDFAs after 8 h and at molar ratio of urea to palm oil of 6.2: 1. Meanwhile, fatty amides (FAs) were synthesized from palm olein and urea by a one-step lipase catalyzed reaction. The use of immobilized lipase as the catalyst for the preparation reaction provides an easy isolation of the enzyme from the products and other components in the reaction mixture. The highest conversion percentage of 96% was obtained when the process was carried for 36 h using urea to palm olein ratio of 5.2: 1.0 at 40 ºC. The method employed offers several advantages such as the use of renewable and abundant of the raw material, simple reaction procedure, environmentally friendly process and high yield of the product. Both CDFAs and the FAs were characterized using Fourier transform infrared (FTIR) spectroscopy, proton nuclear magnetic resonance (1H NMR) technique and elemental analysis. The CDFAs, FAs and fatty hydroxamic acids (which were also synthesized from palm oil) were used as organic compounds to modify natural clay, Na-MMT, (sodium montmorillonite) by an ion exchange process. The clay modification was carried out by stirring the clay particles in an aqueous solution of FAs, CDFAs and fatty hydroxamic acids (FHAs). The interaction of the modifier in the clay layer was characterized by X-ray diffraction (XRD), and Fourier transform infrared (FTIR). Elemental analysis was used to estimate the presence of these fatty nitrogen compounds (FNCs) in the clay. The modified clay was then used in the preparation of the polylactic acid (PLA)/epoxidized palm oil (EPO) blend nanocomposites. The EPO was used as a plasticizer for PLA using chloroform as a solvent for solution casting process of blending PLA/EPO. The FTIR spectra indicate that there are some molecular interactions by intermolecular hydrogen bond between PLA and EPO. All PLA/EPO blends show high thermal stability and significant improvement of mechanical properties compare to those of pure the PLA. The highest elongation at break (about 210%) was obtained when the ratio of PLA/EPO blend was 80/20. Morphological results of PLA/EPO blends show that EPO was miscible with PLA. Reduced viscosities of the blends decrease with increasing amount of EPO indicating that EPO was a good plasticizer for PLA. The nanocomposites were synthesized by incorporating CDFA-MMT, FA-MMT or FHA-MMT into PLA/EPO blends. Preparation of nanocomposites were carried out by solution casting of the modified clay and PLA/EPO blend of the weight ratio of 80/20 which has the highest elongation at break. The highest tensile strength, modulus, and elongation at break of the FA-MMT, FHAMMT, and CDFA-MMT nanocomposites were obtained when 2% of the CDFA-MMT and 3% of both FA-MMT and FHA-MMT loadings were used. These nanocomposites were characterized using XRD, transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and tensile properties measurements. The XRD and TEM results confirm that the products are nanocomposites. PLA/EPO modified clay nanocomposites has higher thermal stability and significant improvement of mechanical properties in comparison with those of the PLA/EPO blend.